Fluidity and acculturation: the case of Pakistani Punjabis in Brunei Darussalam - Zaidi, A.; David, M.K. (Taylor & Francis, 2015)
This paper traces the history of Pakistani Punjabis living in Brunei Darussalam, a community that began its journey long before the country’s establishment as a sovereign country in 1984. The most significant feature of this community is its fluidity because its stay in Brunei is not permanent. This makes the Punjabis a non-local/non-native community, which is markedly different from Punjabi communities living in countries such as Canada, New Zealand, and the UK. While locating the Punjabis within the socio-cultural setting of Brunei Darussalam, the objective of this study is to investigate the lives of Pakistani Punjabis in Brunei as expatriates to gain a deeper knowledge about how their fluid status in Brunei has affected their identity with regard to Punjabiness and Punjabi self, their values and beliefs and whether or not they are a diasporic community.